notice that each of the equations is missing a different variable.
If we can eliminate the variable "a" from the 1st and 3rd, we have a new equation with b's and c's like the 2nd equation
so. from the 3rd a = -6c - 28
sub that into the 1st
6(-6c - 28) - 2b = 18
-36c - 168 - 2b = 18
36c + 2b = -186
b + 18c = -93
let's multiply that by 3
3b + 54c = -279
subtract the 2nd
49c = -245
c = -5
then a = -6(-5) - 28 = 2
3b + 5(-5) = -34
3b = -9
b = -3
a = 2 , b = -3 , c = -5
English - 1. I learned about some Chinese expressions and Chinese cultures. 2. I...
grammer - as the title of a song, which is correct; "I've Learned From You" "I'...
algebra - We just learned equations & inequalities today and im so confused on ...
English - What is the regular verb or verb phrase in these sentences. Most other...
Spanish-Help - We learned different timeframes in We learned timeframes in ...
Algebra 2 - last question, what is the most affective way to solve for slope ...
Adv. Alg/Trig - How would you solve tan(-335) without using a calculator? I got ...
Science - Instinct differs from learned behavior in that instinctive behavior: A...
English - 1. We shouted good expressions together with the sash around the ...
pre alg - How do u find the GCF with exponets in a 7th gr. pre alg. class?